2009
DOI: 10.1242/jcs.031534
|View full text |Cite
|
Sign up to set email alerts
|

Activation of P2X7 receptors causes isoform-specific translocation of protein kinase C in osteoclasts

Abstract: Nucleotides, released in response to mechanical or inflammatory stimuli, signal through P2 nucleotide receptors in many cell types. Osteoclasts express P2X7 receptors (encoded by P2rx7) – Ca2+-permeable channels that are activated by high concentrations of extracellular ATP. Genetic disruption of P2rx7 leads to increased resorption and reduced skeletal response to mechanical stimuli. To investigate whether P2X7 receptors couple to activation of protein kinase C (PKC), RAW 264.7 cells were differentiated into m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 50 publications
2
44
1
Order By: Relevance
“…These findings are consistent with observations in cultures of cerebellar granule neurons, in which activation of P2X7 inhibits GSK3β in a manner dependent upon PKC signaling [13]. Moreover, in osteoclasts, P2X7 couples to activation of various Ca 2+ -sensitive PKC isoforms including PKCα and PKCβ [39]. We have shown previously that activation of P2X7 in osteoblast-like cells couples to PI3K/AKT signaling [17], a pathway associated with GSK3β inhibition [38].…”
Section: P2x7 Promotes Inhibitory Phosphorylation Of Gsk3βsupporting
confidence: 90%
“…These findings are consistent with observations in cultures of cerebellar granule neurons, in which activation of P2X7 inhibits GSK3β in a manner dependent upon PKC signaling [13]. Moreover, in osteoclasts, P2X7 couples to activation of various Ca 2+ -sensitive PKC isoforms including PKCα and PKCβ [39]. We have shown previously that activation of P2X7 in osteoblast-like cells couples to PI3K/AKT signaling [17], a pathway associated with GSK3β inhibition [38].…”
Section: P2x7 Promotes Inhibitory Phosphorylation Of Gsk3βsupporting
confidence: 90%
“…To determine whether P2X7 receptors activate PKC in osteoclasts, Armstrong et al employed murine macrophage RAW 264.7 cells, which differentiate into multinucleated osteoclast-like cells in the presence of RANK ligand. Stimulation of differentiated RAW 264.7 cells with BzATP-induced transient translocation of PKCα to the plasma membrane [60]. In contrast, UTP and low concentrations of ATP, which activate P2 receptors other than P2X7, failed to elicit this response.…”
Section: P2x7 Receptor Signaling In Osteoclastsmentioning
confidence: 87%
“…Moreover, BzATP failed to induce PKC translocation in osteoclasts derived from the bone marrow of P2rx7 −/− mice, demonstrating specificity for P2X7. Translocation was temporally correlated with BzATP-induced elevations in [Ca 2+ ] i and dependent on the presence of extracellular Ca 2+ , thereby implicating P2X7-mediated Ca 2+ influx in PKC activation [60]. A recent study identified signaling through PKC as being essential for enhanced osteoclast survival in response to extracellular acidification [70].…”
Section: P2x7 Receptor Signaling In Osteoclastsmentioning
confidence: 95%
“…Other work has demonstrated that P2X7 receptor activation induces the translocation of NFĸB (Korcok et al, 2004) and an isoform specific PKC in osteoclasts and their precursors (Armstrong et al, 2009). The P2X7 receptor may additionally play a role in the intercellular communication between osteoblasts and osteoclasts, cytoskeletal reorganisation at the sealing zone and the delivery and secretion of lytic granules into the resorption lacunae (Hazama et al, 2009;Jorgensen et al, 2002).…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 98%